IMPACT OF LIFELONG LEARNING PROGRAMS AND BUSINESS DIGITIZATION ON ORGANIZATIONAL ADAPTABILITY - Noniashvili, Maia; Janashia, Nana (Social Economics, 2025)
The study examines the synergistic impact of lifelong learning (LLL) programs and digitalization on organizational adaptability, focusing specifically on small and medium-sized enterprises (SMEs) within Georgia’s business landscape. In today’s increasingly digital and competitive global market, SMEs face immense pressure to remain agile and innovative. This research emphasizes that the integration of employee development initiatives with digital transformation strategies not only enhances organizational resilience but also improves operational efficiency, enabling businesses to better navigate challenges and seize emerging opportunities. Digitalization, as a transformative force, has redefined workflows, optimized processes, and expanded market reach for SMEs. However, the benefits of digital transformation can only be fully realized when employees possess the necessary skills to utilize these technologies effectively. Lifelong learning plays a critical role in equipping the workforce with up-to-date knowledge, fostering adaptability, and ensuring employees can leverage digital tools to drive innovation and productivity. By empowering employees through continuous education, organizations can create a culture of proactive learning and technological competence. Despite their significance to Georgia’s economy, SMEs often encounter barriers to fully embracing digital advancements. These challenges include limited financial resources, inadequate infrastructure, and a lack of structured training programs. As a result, many SMEs struggle to adopt modern technologies and equip their teams with the skills required to sustain competitiveness in a rapidly evolving market. This study highlights these critical gaps and seeks to address how strategic investments in both digital transformation and skill development can enable SMEs to overcome such limitations. Employing a mixed-methods approach, this research explores how the combination of digital tools and lifelong learning programs contributes to key organizational outcomes, such as enhanced efficiency, streamlined decision-making, and improved employee engagement. It also underscores the role of supportive policies in strengthening the digital and educational ecosystems for Georgian SMEs, offering actionable insights into fostering long-term growth and competitiveness. Ultimately, the findings affirm that aligning continuous education with technological adoption is not just beneficial ‒ it is essential for SMEs to thrive in an ever-changing business environment.